2012
DOI: 10.1002/ajh.23161
|View full text |Cite
|
Sign up to set email alerts
|

The aging patient with hemophilia

Abstract: The prospects for many boys born with hemophilia today include a normal life expectancy and minimal to no joint disease. However, despite the availability of safe replacement clotting factor concentrates and effective antiviral treatment, the aging patient with hemophilia today faces many challenges. These include management of their hemophilia as well as the same age‐related health issues as experienced in the general population. While increasing, data on the prevalence of comorbidities and their management i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 89 publications
1
19
0
1
Order By: Relevance
“…Some also have to deal with inhibitors, further complicating the situation . Finally, increasing age in people with haemophilia makes them susceptible to the same medical conditions as the general population .…”
Section: Issues and Counselling Of The Adult With Haemophiliamentioning
confidence: 99%
See 2 more Smart Citations
“…Some also have to deal with inhibitors, further complicating the situation . Finally, increasing age in people with haemophilia makes them susceptible to the same medical conditions as the general population .…”
Section: Issues and Counselling Of The Adult With Haemophiliamentioning
confidence: 99%
“…However, the issues of adults or ageing persons with haemophilia (PWHs) have been less frequently discussed. Ageing with haemophilia is a relatively new phenomenon due to increased life expectancy in this population, as a result of advances in current medical treatment of haemophilia . Adulthood is a period of many personal and social changes, more so with a chronic disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk factors for myocardial infarction and stroke such as diabetes mellitus, obesity, hypercholesterolaemia and smoking in PWH appear to be similar to those of the general population . However, a cross‐sectional study of a cohort of 701 haemophilia patients aged 30 years or older found that the prevalence of hypertension is higher in PWH than in the general population .…”
Section: Introductionmentioning
confidence: 99%
“…This disorder is caused by the deficiency of coagulation factor VIII (FVIII; haemophilia A) or FIX (haemophilia B) [1] and is classified as severe (FVIII <1 IU dL ). While the life expectancy of a patient with haemophilia is increasing and now approaches that of the general male population, they are susceptible to age-related comorbidities such as cardiovascular disease [2]. Therefore, it is necessary to manage cardiovascular events in elderly patients with haemophilia in a different manner to patients without haemophilia [3,4].…”
Section: Dear Sirmentioning
confidence: 99%